HRM PRACTICESON EMPLOYEE PERCEPTION AND ITS EFFECT ON ORGANIZATIONAL COMMITMENT - Dr. Aajaz Ahmad Hajam; Alphonsa S John (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The corporate environment has changed dramatically since the start of globalization, both in terms of complexity and dynamism. Companies are coping with shifting market conditions, changing workforce demographics and diversity, technological advancements, increased customer and quality focus, a talent shortage, and shifting economic realities (Noe, 2002). In order to attain long-term sustainability and total organizational success, it is crucial for businesses to continuously alter their business strategy, policies, and practices to conform to the shifting needs of the business environment. In other words, firms are compelled to implement and successfully manage change continuously (Bridges & Mitchell, 2000; Kanter, 1985). Despite the fact that organizations need to manage change more effectively, 70% of change initiatives fail (Beer &Nohria, 2000), and this failure rate has remained stable over time. Insufficient attention to issues relating to people is one of the most frequently mentioned causes of change implementation failure (Spiker & Lesser, 1995; Kotter, 1995). During the 1990s, there has been widespread recognition of the significance of employees, their psychological reactions, and their behavior during organizational transformation; yet, in practice, managers do not place enough emphasis on these concerns (Becker & Gerhart, 1996). Others who have conducted empirical studies in this area concur with this viewpoint. For instance, research on the implementation of a customer relationship management (CRM) project at three banks in New Zealand and discovered that firms tend to prioritize technological difficulties while ignoring issues relating to people.